SOCIALIZATION OF FACTORS CAUSING PENDING CLAIMS AT RSI. IBNU SINA 'YARSI' PADANG - Yastori, Yastori (LPPM Univ. Ibn Khaldun Bogor, 2023)
Coding accuracy is closely related to claims or financial hospital financing. The claim made by the health insurance is the submission of the cost of treating the patient's health insurance participant by the hospital to the health insurance party which is carried out collectively and billed to the health insurance funder every month. Based on a preliminary study on the incidence of pending claims at RSI. Ibnu Sina 'Yarsi' Padang occurred due to inaccuracies in giving the code or incompleteness, incompatibility of supporting document files, or evidence that was in line with the diagnosis written on the medical record documentation. This Community Service Activity (PKM) has been carried out on October 17, 2022, at RSI. Ibnu Sina 'Yarsi' Padang which was attended by 19 participants to provide understanding and knowledge related to examples of factors that affect pending claims cases. The method of implementation is in the form of socialization and delivery of case examples as well as discussion of the discussed cases, then a session of filling in the link of questions related to the material is carried out as well as interviews and direct discussions with medical record officers and participants present during the discussion session. The activity went smoothly, it could be seen that the participants began to understand and were able to analyze the influencing factors and coding rules related to the pending claim case at the RSI Ibnu Sina 'Yarsi' Padang.